Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1248/bpb.b12-01088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acyl-CoA Thioesterase in Mouse Mesenteric Lymph Nodes

Abstract: Acyl-CoA thioesterases (ACOTs) are a group of enzymes that catalyze the hydrolysis of fatty acyl-CoAs to free fatty acids and CoA, with the potential to regulate the intracellular levels of these molecules. In this study, we show that a cytosolic isoform, ACOT7, is expressed at a significant level in the mesenteric lymph nodes (MLNs) of mice. While crude preparations of the mesenteric visceral fat contained significant levels of palmitoyl-CoA thioesterase activity, enzyme activity was concentrated 6.9-fold in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Importantly, ACOT1 and ACOT2 are 93.7% homologous (24), and therefore the antibody generated for these studies recognizes both ACOT1 and ACOT2. However, ACOT2 is exclusively a mitochondrial protein (23), and previous groups have shown that ACOT2 runs below ACOT1 on SDS-PAGE gels (25). Therefore, to show the specificity of our antibody, we compared our samples to those of mitochondrial preparations from mouse liver overexpressing Acot2 (23).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, ACOT1 and ACOT2 are 93.7% homologous (24), and therefore the antibody generated for these studies recognizes both ACOT1 and ACOT2. However, ACOT2 is exclusively a mitochondrial protein (23), and previous groups have shown that ACOT2 runs below ACOT1 on SDS-PAGE gels (25). Therefore, to show the specificity of our antibody, we compared our samples to those of mitochondrial preparations from mouse liver overexpressing Acot2 (23).…”
Section: Resultsmentioning
confidence: 99%
“…Among ACOT family members, ACOT1 (cytosolic), ACOT2 (mitochondrial), and ACOT7 (cytosolic) have been well characterized for their enzymatic properties. 4 These ACOTs share a common feature in that their expression is markedly induced by ligands for peroxisome proliferator-activated receptor α (PPAR α ), a nuclear receptor that regulates lipid metabolism-related genes such as the fibrate class of hypolipidemic drugs. 4 Moreover, ACOT1 and ACOT2 have been implicated in fatty acid catabolism, as emphasized by their upregulation in the liver and heart of fasted or high-fat-diet fed animals.…”
Section: Discussionmentioning
confidence: 99%
“… 4 These ACOTs share a common feature in that their expression is markedly induced by ligands for peroxisome proliferator-activated receptor α (PPAR α ), a nuclear receptor that regulates lipid metabolism-related genes such as the fibrate class of hypolipidemic drugs. 4 Moreover, ACOT1 and ACOT2 have been implicated in fatty acid catabolism, as emphasized by their upregulation in the liver and heart of fasted or high-fat-diet fed animals. 47 , 48 , 49 , 50 However, ACOT7 has two orders of magnitude higher enzyme activity than ACOT1 and ACOT2, and its expression is prominent in neurons of the central and peripheral nervous systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations